2014
DOI: 10.5694/mja14.00021
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening rates for women vaccinated against human papillomavirus

Abstract: Despite education messages provided to young women, our results suggest that vaccinated women are being screened at lower rates than unvaccinated women in Australia. While some degree of undermatching of women in the study may have occurred, this cannot wholly explain our findings. Effective implementation of Individual Healthcare Identifiers to health records, including registry records, is needed to prevent potential undermatching of individuals in future linkage studies. In the meantime, efforts to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 9 publications
2
36
4
Order By: Relevance
“…Our findings of higher Pap testing among women receiving HPV vaccination were similar to a previous study in the U.S. [6] and a study from the U.K. [26] but not consistent with the results of an Australian study [27]. Both the U.K. and Australia have had national programs focused on HPV catch-up vaccination while there has been no comparable program in the U.S. Additionally, variation between our study and the Australian study could be due to differences in study design as their study used linked data with unknown matching sensitivity and they did not account for race/ ethnicity or any socioeconomic factors [27].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Our findings of higher Pap testing among women receiving HPV vaccination were similar to a previous study in the U.S. [6] and a study from the U.K. [26] but not consistent with the results of an Australian study [27]. Both the U.K. and Australia have had national programs focused on HPV catch-up vaccination while there has been no comparable program in the U.S. Additionally, variation between our study and the Australian study could be due to differences in study design as their study used linked data with unknown matching sensitivity and they did not account for race/ ethnicity or any socioeconomic factors [27].…”
Section: Resultssupporting
confidence: 64%
“…Both the U.K. and Australia have had national programs focused on HPV catch-up vaccination while there has been no comparable program in the U.S. Additionally, variation between our study and the Australian study could be due to differences in study design as their study used linked data with unknown matching sensitivity and they did not account for race/ ethnicity or any socioeconomic factors [27].…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…This is in contrast to 2 studies in adults, which demonstrated that greater than 90% of participants reported high intention to receive a Pap test after vaccination. 3,4 Our results, combined with another finding in a study of 20-29 year-old women which demonstrated that vaccinated women are less likely to participate in screening compared to unvaccinated women, 5 suggest that educational messages given at the time of HPV vaccination and at followup visits should focus on the importance of following future Pap screening recommendations.…”
Section: Discussionmentioning
confidence: 57%
“…Although two studies in adults demonstrated high intention to participate in Pap screening after vaccination, 3,4 a study in 20-29 year-old women in Australia demonstrated that vaccinated vs. unvaccinated women were less likely to participate in screening. 5 Intention is defined as an individual's motivation to perform a behavior. 6 Self-efficacy is defined as confidence in oneself to exert personal control to perform a behavior.…”
Section: Introductionmentioning
confidence: 99%